MONITORING PADA UNIT GRADER 825A-2 DENGAN ALAT DATA LOGGER BERBASIS INTERNET OF THINGS PT KALIMANTAN PRIMA PERSADA JOBSITE INDE - Pratama, Argiansyah Bayu; Monasari, Ratna; Khambali, Khambali; Pratama, Rizki Priya (Universitas Muhammadiyah Metro, 2025)
The GD825A-2 Grader Unit at PT Kalimantan Prima Persada Jobsite Indehas an average Physical Availability (PA) value of 89%, below the target of 92%, due to the high unscheduled breakdown. Manual monitoring of sensor parameters is one of the causes of delays in damage detection. This study designs and implements an Internet of Things (IoT)-based monitoring tool with a data logger to read sensor data in real-time. The methods used include testing sensor accuracy against manual measuring instruments, descriptive statistical analysis, errors, and process capability tests. The results show a temperature sensor error rate of 2%, oil pressure 5%, and engine rotation 0.11%. All sensors are also proven to be stable, within statistical control limits, and have decent process capabilities. This system allows for accurate, fast, and remote monitoring of unit conditions, thereby reducing the risk of breakdown, and optimizing maintenance costs for the GD825A-2 unit.